Transcriptome analysis expands the potential roles of quorum sensing in biodegradation and physiological responses to microcystin - Zeng, Yan-Hua; Cheng, Ke-Ke; Cai, Zhong-Hua; Zhu, Jian-Ming; Du, Xiao-Peng; Wang, Yan; Zhou, Jin (The Science of the total environment, 2021)
Bacterial degradation is one of the most efficient ways to remove microcystins (MCs), the most frequently detected toxin in cyanobacterial blooms. Using Novosphingobium sp. ERW19 as a representative strain, our laboratory previously demonstrated that quorum sensing (QS), the cell density-dependent gene regulation system, positively regulates biodegradation of MCs via transcriptional activation of mlr-pathway-associated genes. Increasing evidence indicates that QS is involved in a wide spectrum of regulatory circuits, but it remains unclear which physiological processes in MC degradation besides the expression of MC-degrading genes are also subject to QS-dependent regulation. This study used transcriptome analysis to identify QS-regulated genes during degradation of MCs. A large percentage (up to 32.6%) of the genome of the MC-degrading bacterial strain Novosphingobium sp. ERW19 was significantly differentially expressed in the corresponding QS mutants. Pathway enrichment analysis of QS-regulated genes revealed that QS mainly influenced metabolism-associated pathways, particularly those related to amino acid metabolism, carbohydrate metabolism, and biodegradation and metabolism of xenobiotics. In-depth functional interpretation of QS-regulated genes indicated a variety of pathways were potentially associated with bacterial degradation or physiological responses to MCs, including genes involved in cell motility, cytochrome P450-dependent metabolism of xenobiotics, glutathione S-transferase (GST), envelope stress response, and ribosomes. Furthermore, QS may be involved in regulating the initial and final steps of the catabolic pathway of phenylacetic acid, an intermediate product of MC degradation. Collectively, this global survey of QS-regulated genes in a MC-degrading bacterial strain facilitates a deeper understanding of QS-controlled processes that may be important for bacterial degradation of MCs or may contribute to the physiological responses of bacteria to MCs. [Display omitted] •Quorum sensing (QS) is a global gene regulatory system in microcystin degradation.•QS affects critical metabolism pathways during microcystin degradation.•QS-regulated behaviors are linked to biodegradation or responses to microcystin.•Expression of key genes in phenylacetic acid catabolism is controlled by QS.